Potential Applications and Antifungal Activities of Engineered Nanomaterials against Gray Mold Disease Agent Botrytis cinerea on Rose Petals - Hao, Yi; Cao, Xiaoqian; Ma, Chuanxin; Zhang, Zetian; Zhao, Na; Ali, Arbab; Hou, Tianqi; Xiang, Zhiqian; Zhuang, Jian; Wu, Sijie; Xing, Baoshan; Zhang, Zhao; et al. (Frontiers in Plant Science, 2017)
Nanoparticles (NPs) have great potential for use in the fields of biomedicine, building materials, and environmental protection because of their antibacterial properties. However, there are few reports regarding the antifungal activities of NPs on plants. In this study, we evaluated the antifungal roles of NPs against Botrytis cinerea, which is a notorious worldwide fungal pathogen. Three common carbon nanomaterials, multi-walled carbon nanotubes, fullerene, and reduced graphene oxide, and three commercial metal oxidant NPs, copper oxide nanoparticles (CuO NPs), ferric oxide nanoparticles (Fe2O3 NPs), and titanium oxides nanoparticles (TiO2 NPs), were independently added to water-agar plates at 50-mg/L and 200-mg/L concentrations. Detached rose petals were inoculated with spores of B. cinerea and co-cultured with each of the six nanomaterials. The sizes of the lesions on infected rose petals were measured at 72 h after inoculation, and the growth of fungi on the rose petals was observed by scanning electron microscopy. The six NPs inhibited the growth of B. cinerea, but different concentrations had different effects: 50 mg/L of fullerene and CuO NPs showed the strongest antifungal properties among the treatments, while 200 mg/L of CuO and Fe2O3 showed no significant antifungal activities. Thus, NPs may have antifungal activities that prevent B. cinerea infections in plants, and they could be used as antifungal agents during the growth and post-harvesting of roses and other flowers. To the authors’ best knowledge, this is the first in planta assay illustrating the antimicrobial activities of NPs against a fungal pathogen.